Answer:
a. [tex]f^{-1}(x)=\frac{x-5}{3}[/tex].
b. See below
Step-by-step explanation:
The given function is: [tex]f(x)=3x+5[/tex]
To find the inverse function, we let [tex]y=3x+5[/tex].
We interchange x and y to obtain: [tex]x=3y+5[/tex].
We now solve for y;
First add -5 to both sides of the equation;
[tex]x-5=3y[/tex].
Divide both sides by 3
[tex]\frac{x-5}{3}=y[/tex].
Or
[tex]y=\frac{x-5}{3}[/tex].
The inverse function is [tex]f^{-1}(x)=\frac{x-5}{3}[/tex].
b.
Let us now verify that;
[tex]f^{-1}(f(x))=x[/tex]
[tex]\implies f^{-1}(f(x))=\frac{3x+5-5}{3}[/tex]
[tex]\implies f^{-1}(f(x))=\frac{3x}{3}[/tex]
[tex]\implies f^{-1}(f(x))=\frac{x}{1}[/tex]
[tex]\implies f^{-1}(f(x))=x[/tex]
[tex]\boxed{Q.E.D}[/tex]